1994
DOI: 10.1016/s0007-8506(07)62226-4
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations and Surface Generation in Slab Milling

Abstract: SUMMARY:In slab milling the quality of the machined surface is directly influenced by the dynamic behaviour of the machine tool. In addition to the cycloidical microgrooves, the dynamic relative motion between the workpiece and tool is superimposed on the machined surface. In general these vibrations cannot be directly identified by investigat~ng the machined surface. By the application of a special purpose milling cutter, microgrooves are generated which are identifiable and from which the relative motions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…It was generally accepted that wave patterns left on the work piece from a previous pass greatly effects the current pass, however, it is demonstrated that tool passes two or more turns prior to the current pass also have an effect. The phase difference and frequency of the waves etched into the surface of the prior turns interact with one another, and if the conditions are correct, interact in a critical way that produces increasing amplitude vibrations [16]. While Tlusty was able to theorize that chatter stabilizes at a certain point due to the tool leaving the work piece, Kondo et al set off to prove this theory [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was generally accepted that wave patterns left on the work piece from a previous pass greatly effects the current pass, however, it is demonstrated that tool passes two or more turns prior to the current pass also have an effect. The phase difference and frequency of the waves etched into the surface of the prior turns interact with one another, and if the conditions are correct, interact in a critical way that produces increasing amplitude vibrations [16]. While Tlusty was able to theorize that chatter stabilizes at a certain point due to the tool leaving the work piece, Kondo et al set off to prove this theory [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assuming the simple harmonic motion, the form of u ( z, t ) = U ( z ) sinωt, and v ( z, t ) = V ( z ) cosωt (10) where ω frequency of oscillation and U and V are the amplitudes of u and v . Substituting equations (10) into equations (6) and 7, they can be re-written as:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…It was generally accepted that wave patterns left on the work piece from a previous pass greatly effects the current pass, however, it is demonstrated that tool passes two or more turns prior to the current also have an effect. The phase difference and frequency of the waves etched into the surface of the prior turns interact with one another, and if the conditions are correct, interact in a critical way that produces increasing amplitude vibrations [10]. While Tlusty was able to theorize that chatter stabilizes at a certain point due to the tool leaving the work piece, [12] set off to prove this theory.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research reported that the RMS values reveal a strong correlation between cutting conditions and signals in micro-cutting at sub-micrometer scales. [8,9] Therefore, the AE signals were converted to RMS values. Fig.2 shows a schematic of the experimental method and procedure.…”
Section: Experimental Cutting Conditionsmentioning
confidence: 99%